States of stress and slip partitioning in a continental scale strike-slip duplex: Tectonic and magmatic implications by means of finite element modeling - Iturrieta, Pablo Cristián; Hurtado, Daniel E.; Cembrano, José; Stanton-Yonge, Ashley (Earth and planetary science letters, 2017)
Orogenic belts at oblique convergent subduction margins accommodate deformation in several trench-parallel domains, one of which is the magmatic arc, commonly regarded as taking up the margin-parallel, strike-slip component. However, the stress state and kinematics of volcanic arcs is more complex than usually recognized, involving first- and second-order faults with distinctive slip senses and mutual interaction. These are usually organized into regional scale strike-slip duplexes, associated with both long-term and short-term heterogeneous deformation and magmatic activity. This is the case of the 1100 km-long Liquiñe–Ofqui Fault System in the Southern Andes, made up of two overlapping margin-parallel master faults joined by several NE-striking second-order faults. We present a finite element model addressing the nature and spatial distribution of stress across and along the volcanic arc in the Southern Andes to understand slip partitioning and the connection between tectonics and magmatism, particularly during the interseismic phase of the subduction earthquake cycle. We correlate the dynamics of the strike-slip duplex with geological, seismic and magma transport evidence documented by previous work, showing consistency between the model and the inferred fault system behavior. Our results show that maximum principal stress orientations are heterogeneously distributed within the continental margin, ranging from 15° to 25° counter-clockwise (with respect to the convergence vector) in the master faults and 10–19° clockwise in the forearc and backarc domains. We calculate the stress tensor ellipticity, indicating simple shearing in the eastern master fault and transpressional stress in the western master fault. Subsidiary faults undergo transtensional-to-extensional stress states. The eastern master fault displays slip rates of 5 to 10 mm/yr, whereas the western and subsidiary faults show slips rates of 1 to 5 mm/yr. Our results endorse that favorably oriented subsidiary faults serve as magma pathways, particularly where they are close to the intersection with a master fault. Also, the slip of a fault segment is enhanced when an adjacent fault kinematics is superimposed on the regional tectonic loading. Hence, finite element models help to understand coupled tectonics and volcanic processes, demonstrating that geological and geophysical observations can be accounted for by a small number of key first order boundary conditions. •Distribution of stress and slip in active continental margins depends on transcurrent faults geometry.•We propose a finite element model that consider the elasto–plastic behavior of fault zones.•Strike-slip duplex geometry strongly influences individual faults state of stress.•Adjacent faults interaction plays a key role in how slip and stress are distributed.•Magma migration through faults is favored near a fault intersection.